Analisis Pengaruh Profitabilitas, Likuiditas, dan Struktur Aset Terhadap Struktur Modal Perusahaan dengan Ukuran Perusahaan Sebagai Variabel Moderasi: Studi Empiris pada Perusahaan Manufaktur Sub Sektor Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023 - Indah Wahyuni; Andy Dwi Bayu Bawono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of profitability, liquidity, and asset structure on the capital structure of manufacturing companies in the industrial subsector listed on the Indonesia Stock Exchange during the period 2021-2023, as well as to examine the role of company size as a moderating variable in these relationships. The purposive sampling method was used to select a representative research sample. The data were analyzed using multiple regression and Moderated Regression Analysis (MRA). The results show that profitability and liquidity have a significant effect on the company’s capital structure, while asset structure does not have a significant impact. Furthermore, company size does not moderate the influence of profitability, liquidity, or asset structure on capital structure. This study indicates that internal factors such as profitability and liquidity are the main determinants in forming the capital structure of manufacturing companies, whereas company size neither strengthens nor weakens these relationships.